(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The phenomenon of interaction between material substances is the basis of the natural evolution of all things. The interaction of matter occurs through contacts that physics has identified in electromagnetic, gravitational or other nature waves. Electromagnetic waves in particular have a dual corpuscular wave nature, one and the other are like two sides of the same coin, inextricably linked. The origin of the universe in space-time, according to quantum mechanics, is synchronous with the origin of the wave-particles themselves, but it does not reveal to us how they were generated. We must necessarily argue that at the very moment of the birth of electromagnetic waves, space-time also assumed a knowable dimension. This article investigates the evolution of the universe as an epiphenomenon of the mass-energy interaction of matter through the waves generated by it in cosmic space-time. In this investigation I let myself be carried by those same waves that move everything, in the hope that sooner or later they will illuminate my vision of the world.